Towards the Biomarker-Driven Development and their Global Impact in the Evidence-Based Clinical Practice of Personalized and Precision Healthcare Services - Suchkov, Sergey; Demidova, Valentina; Tsytsarev, Vassiliy; Cotter, Philip D.; Cheng, R. Holland; Blokh, Sofya; Smith, David; Polyakova, Veronika; Zemskov, Vladimir; Murphy, Shawn; Grishina, Tatiana; Wu, Alan; et al. (British Journal of Healthcare and Medical Research, 2024)
Drug development continues to move in the direction of the development of clinical practice as applicable to Personalized and Precision Medicine (PPM), - where ideally the most effective therapy or treatment is determined by the genetic makeup of the patient.